Polityka finansowa w rolnictwie polskim w świetle wymagań wspólnej polityki rolnej UE - Antoniszyn, Emil (Financial Policy in Polish Agriculture in the Light of Requirements of Common Agriculture Policy of the European Union, 2006)
The resolutions of the Berlin summit established the general strategy of development and enlargement of the Union. The additional sources budgeted within the Union funds comprise: • pre-accession financial aid (PHARE, ISPA, SAP ARD) to implement the principles of the Common Agricultural Policy in the new member states, • structural funds. The above mentioned issues were regulated by the directives of the Council; signature WE 1255/1999. The sum of the pre-accession sources was established for 3.1 milliard euro annually (until 2006), out of which 0.52 milliard was to support agriculture, 1.04 milliard for structural aid and 1.56 milliard for the PHARE programme. Altogether the Union allocated 21.7 milliard euro for this help, out of which agriculture obtained 3.6 milliard euro plus roughly 1.5 milliard euro from PHARE. It might be estimated that an annual aid for the Polish agriculture and the countryside prior to the accession could have amounted to about 220 million euro. It was to account for one fifth of the Polish state expenditure in the development of the Polish agriculture and the rural areas if the conditions of its effective use were created. Initially, financial help was taken from PHARE, which indicates that only about two thirds of designated sources had not been used before Poland entered the European Union. The separate sources for the European Union enlargement were allocated and amounted to 4.1 milliard euro in the first year and 14.2 milliard euro in 2006, out of which 1.6 milliard euro in 2002 and 3.4 milliard euro in 2006 was allocated for agriculture. It is generally known that the Union underestimated the sources for the European Union enlargement, especially for agriculture. Paradoxically it its budget the Union spends less than two thirds of its sources on agriculture while in the budget of the EU 15 it projected almost a half of all the budget, though, the needs of eastern and central European agriculture are bigger than the Union's. The condition of the Polish agriculture influences the whole economy. The political transformation has been seen in the agriculture as an economic pressure. This has led to the decrease in the profitability of agriculture by 50 percent for nearly the last 10 years. And there is still a gradual drop in production after 1989.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1109, s. 25-33